Pro-Bolsonaro discourse and military police officers' narratives during COVID-19 pandemic (Research, Society and Development, 2022)
The article seeks to identify and analyze the presence of a pro-Bolsonaro discourse during the covid-19 pandemic in military police officers’ statements about the new coronavirus. The corpus of the research is based on a questionnaire answered by military police during the covid-19 pandemic, and speeches by President Jair Messias Bolsonaro, as well as his ministerial team, between the months of March to August 2020, systematized by Conectas Direitos Humanos. It uses Norman Fairclough’s Critical Discourse Analysis (CDA). As a result, it is verified that the military police officers’ statements report the discourse built by the president of Brazil, reproducing narratives that deny the pandemic and encourage false therapies. Therefore, the need for more in-depth research on the subject should be considered to be carried out, in view of the existing limits between conservative pro-Bolsonaro thinking and the professional performances of the military police in times of a pandemic.